Does Real-time Feedback Guide Devices Improve the Quality of Chest Compressions in the Bystander (Naves) Provider? - Thamir AlSayed; Samer Al Haliq; Faisal Katbi; Mohannad Alghamdi; Mohammed Almulhim (Journal of Emergencies, Trauma and Shock)
Introduction: Cardiopulmonary resuscitation (CPR) is an important lifesaving technique that must taught to everyone. As most cardiac arrests occur outside of the hospital, training the general population in the recognition of cardiac arrest and performing high-quality CPR is vital. Thus, this study aimed to compare the chest compression quality data (rate, depth, and fraction) with and without the use of feedback devices during CPR. Methods: A crossover observational study was carried out at a tertiary hospital in September 2021. Five hundred and seventeen 1st-year university students were recruited, and the response rate was 90% (465). A feedback device was used to collect data. The data were numerically coded and statistical software (SPSS 21) was used to perform descriptive and inferential statistical analysis, including a paired t-test. Results: The mean compression rate with feedback was statistically significantly lower after performing one cycle of CPR (mean difference: −5.610; 95% confidence interval [CI]= −7.987–−3.233; P < 0.001), the difference between mean compression depth with and without feedback was not statistically significant (mean difference: = −0.006; 95% CI = −0.190–0.177; P = 0.944), and the mean compression target (%) with feedback was statistically significantly higher (mean difference: −15.951; 95% CI = −17.894–−14.009; P < 0.001). Conclusions: We found that the use of feedback devices during layperson-simulated CPR scenarios significantly improved the quality of chest compression in terms of depth and rate and resulted in more guidelines adherence. Moreover, national programs for CPR education should be implemented.